Perbandingan Tingkat Stres Mahasiswa Empat Angkatan Program Studi Teknik Industri dengan Metode Skoring dari Health and Safety Executive - Rahdiana, Nana (Jurnal Sistem Teknik Industri, 2020)
Stress can be interpreted as psychological pressure that can cause both physical and mental illness. Stress on students can be anxious or tense that occurs in lectures, work assignments and other academic activities. Stress can influence students in completing their studies. This study aims to determine differences in stress levels between students in 2015, 2016, 2017 and 2018 Industrial Engineering Study Program, University of Buana Perjuangan Karawang in 2019. This research method is an observational analytic study with approach cross sectional. Data was obtained by distributing questionnaires to 90 student respondents who were divided proportionally per class by following the Slovin formula used was sampling technique simple random sampling. The. This study used the HSE questionnaire instrument, the data were analyzed statistically with the Independent T-test and Anova, as well as the correlation test with the method Point-biserial Correlation from Pearson and Spearmen's Rho. From the results of this study there are differences in stress levels between students in 2015, 2016, 2017 and 2018, where students in 2015 tend to be low stressed by 50.0%, while the classes of 2016, 2017 and 2018 tend to be moderate stress with a percentage of 55,6%; 65.4%; and 64.7%. Sex, age and work status of students do not affect stress levels, and do not have a significant relationship with stress levels.